UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DENGAN MENERAPKAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE (SSCS) DI KELAS X IIS 1 MAN 1 PEKANBARU TAHUN PELAJARAN 2019/2020 - Syafni Ermayulis (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The purpose of this study was to describe the effect of applying the SSCS model (Search, Solve, Create, and Share) on student learning outcomes in economic subjects in class X IIS 1 in Madrasah Aliyah Negeri 1 Pekanbaru in the 2019/2020 academic year. Research conducted at MAN 1 Pekanbaru precisely in class X iis 1, the method used is the observation of the activities of teachers and students in 2 cycles. Data collection technique used is the percentage technique that compares the appearance of the whole multiplied by 100%. The instrument was in the form of an observation sheet of student activities, while the test of learning outcomes to determine individual completeness was determined KKM 80 and completeness classically 75% had reached the minimum completeness standard. by research instruments in the form of written tests, and observation sheets. This instrument used is an objective test in the form of multiple choice. The data collected is quantitative data. The results showed that: the application of the learning model SSCS learning model (Search, Solve, Create, and Share) can improve the economic learning outcomes of students of class X IIS 1 MAN 1 Pekanbaru on the subject matter of Business Entity Concepts in the Indonesian Economy even semester 2019 / 2020 The results of this study are expected to be useful for the improvement and improvement of learning outcomes of students, especially in the field of economic studies.